Behavioral Context of Blue and Fin Whale Calling for Density Estimation - Sirovic, Ana; Calambokidis, John (2014)
This is the first annual report for this project, in which we will determine the context-appropriate call production rates for blue and fin whales in the Southern California Bight, with the end goal of facilitating density estimation from passive acoustic data. Prepared in collaboration with the Cascadia Research Collective, Olympia, WA.